2008
DOI: 10.1364/oe.16.015754
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of conversion efficiency for multi-junction solar cells by incorporation of Au nanoclusters

Abstract: We studied the photoluminescence (PL) and photovoltaic current-voltage characteristics of the three-junction InGaP/InGaAs/Ge solar cells by depositing Au nanoclusters on the cell surface. The increases of the PL intensity and short-circuit current after incorporation of Au nanoclusters are evident. An increase of 15.3% in energy conversion efficiency (from 19.6 to 22.6%) is obtained for the three-junction solar cells in which Au nanoclusters have been incorporated. We suggest that the increased light trapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…These properties make GNPs favourable for innumerable applications in medical, electronics, materials science, alternative energy generation, environmental restoration, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Available methods for nanoparticle synthesis use toxic chemicals either in the form of reducing agents to reduce various metal salts to their corresponding nanoparticles or as stabilizing agents to prevent nanoparticles from agglomeration [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These properties make GNPs favourable for innumerable applications in medical, electronics, materials science, alternative energy generation, environmental restoration, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Available methods for nanoparticle synthesis use toxic chemicals either in the form of reducing agents to reduce various metal salts to their corresponding nanoparticles or as stabilizing agents to prevent nanoparticles from agglomeration [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the use of plasmonic metal nanoparticles (NP) to enhance the light absorption of silicon solar cell has attracted much attention. The more effective optical absorption is caused by scattering from the metallic nanoparticles [1]. The incident light interacts with the metal NP very effectively by coupling surface Plasmon [2] over cross sections much larger than the NP's geometrical cross section [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nakayama et al carried research on Ag nanoparticles for improving light absorption in GaAs solar cells, which demonstrated that the efficiency was enhanced by 5.9% [11]. The above-mentioned experiments show that SPs are an effective way for light trapping [12]. However, little theoretical work has been carried out to quantify the effectiveness of plasmonic light trapping structure, especially to evaluate the effectiveness of light trapping over the full spectrum.…”
Section: Introductionmentioning
confidence: 99%